Analysis the Development of Oyster Cultivation (Crassostrea Sp.) on Coastal Communities’s Income - Dzikira, Teuku Muharna; Purwoko, Agus; Rini, Endang Sulistya (Journal of Environmental and Development Studies, 2022)
This study aims to determine the effect of cultivation on the income of the coastal community of Alue Naga Village, Syiah Kuala District, Banda Aceh City, which was carried out with mentoring, cultivation and technology variables. Seeing the extent of the contribution, the impact of mentoring on oyster cultivation on people's incomes. The research method used is descriptive quantitative, with data processing method using Statistical Packag For The Sociences (SPSS). The population in this study is the entire community of Alue Naga who cultivate oysters from 4 hamlets namely Musafir, Bunot, Kuntara and Podiamat hamlets totaling 164 people with a sample of 62 people. The results showed that the income contribution was 37.47% (assistance) and the income contribution was 23.72% (without assistance) with the difference in the value of income per individual, the difference was Rp. 639,000 thousand rupiah per month. From these results simultaneously mentoring and technology variables have a positive and significant effect on income, while the cultivation variable has no (negative) and insignificant effect on income, for more details it has been presented in this study.